The hydration effect on palm oil fuel ash concrete containing eggshell powder. (January 2019) - Abd Khalid, NH; Abdul Rasid, N N; Mohd. Sam, A R; Abdul Shukor Lim, NH; Zardasti, L; Ismail, M; Mohamed, A; Majid, Z A
Abstract: Hydration reaction is an exothermic reaction, where heat is released during the hardening process of concrete until it reached stable low energy stated the hydration temperature describes the hardening behaviour of concrete. This paper presents the hydration effect on Palm Oil Fuel Ash (POFA) concrete containing Eggshell Powder (ESP)—combination of silica and calcium oxide (SiO2 -CaO) that has becoming a new trend to improve catalyst characteristic of ESP in POFA concrete. In this study, ESP was combined between two types of POFA: Ground and Unground POFA (GPOFA and UPOFA). Initially, the optimum mix proportion was determined by two parameters: workability and compressive strength of POFA-ESP concrete. Higher compressive strength with sufficient workability of concrete was prioritized as optimum mix proportion. Overall, the compressive strength of concrete showed increment; GPOFA-ESP concrete gained superior compressive strength as compared to normal concrete (NC) and UPOFA-ESP concrete. The desired optimum mix proportion of the samples were investigated further under hydration reaction test. The overall hydration temperature for GPOFA-ESP concrete was slightly higher as compared to NC and UPOFA-ESP concrete. All in all, ESP has potential to act as a low catalyst in POFA concrete.